2015
DOI: 10.1128/jvi.00515-15
|View full text |Cite
|
Sign up to set email alerts
|

Interregional Coevolution Analysis Revealing Functional and Structural Interrelatedness between Different Genomic Regions in Human Mastadenovirus D

Abstract: Human mastadenovirus D (HAdV-D) is exceptionally rich in type among the seven human adenovirus species. This feature is attributed to frequent intertypic recombination events that have reshuffled orthologous genomic regions between different HAdV-D types. However, this trend appears to be paradoxical, as it has been demonstrated that the replacement of some of the interacting proteins for a specific function with other orthologues causes malfunction, indicating that intertypic recombination events may be delet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…The detected recombined region of the first event was from position 15 983‐16 983 bp in the strain sequence, affecting the coding region of the L3 :pV and identified by six of seven recombination detection algorithms with significant support ( P < 0.05). In contrast, the recombined region of the second event covered the position from between 17 854 and 19 750 bp in the strain sequence, affecting the loops of the hexon, L1 and L2 (Figure B), which have been demonstrated to be frequently recombined in this species . The second event was detected independently by the seven algorithms in RDP with strong support ( P < 10 −14 ) (Figure C).…”
Section: Resultsmentioning
confidence: 94%
“…The detected recombined region of the first event was from position 15 983‐16 983 bp in the strain sequence, affecting the coding region of the L3 :pV and identified by six of seven recombination detection algorithms with significant support ( P < 0.05). In contrast, the recombined region of the second event covered the position from between 17 854 and 19 750 bp in the strain sequence, affecting the loops of the hexon, L1 and L2 (Figure B), which have been demonstrated to be frequently recombined in this species . The second event was detected independently by the seven algorithms in RDP with strong support ( P < 10 −14 ) (Figure C).…”
Section: Resultsmentioning
confidence: 94%
“…Exactly in HAdV-D strains it is often observed that homologous recombination has a driving force in adenovirus evolution (Crawford-Miksza and Schnurr 1996;Gonzalez et al 2015;Ismail et al 2018a;Kaján et al 2017;Robinson et al 2013;Walsh et al 2009). Predominantly, intraspecies recombination events are common, but intergenus recombinants have also been reported already: the head domain of the porcine adenovirus 5 (genus Mastadenovirus) fibre seems to be of atadenoviral origin (Nagy et al 2002), though a porcine atadenovirus has not been discovered yet.…”
Section: Adenovirusesmentioning
confidence: 99%
“…Further evaluation of our phylogenetic and recombination analysis data (Table 1 and Figure 1) revealed that in addition to the already mentioned types, several additional types appear to have contributed to the final composition of the HAdV-84 genome, through multiple recombination events. Recombination is one of the major driving forces in HAdV evolution (Gonzalez et al, 2015;Robinson et al, 2013). The penton base's variable loop is most similar to that of HAdV-8, while the remaining penton base backbone is more similar to HAdV-43.…”
mentioning
confidence: 99%